IMPLEMENTING RECIPROCAL TEACHING METHOD IN IMPROVE THE STUDENTS’ READING COMPREHENSION ABILITY - Syaiful Islam (ETERNAL (English, Teaching, Learning and Research Journal), 2020)
This research was designed to improve the students’ reading comprehension in English through the implementation of Reciprocal Teaching Method. The research employed a collaborative classroom action research design in which the researcher and the collaborative teacher worked together in preparing a suitable procedure of Reciprocal Teaching Method, designing the lesson plan, determining of the criteria of success, implementing the action, observing, and doing reflections. The subjects of this research were 40 students of Grade XI BHS 2 at MA. Nurul Jadid Problolinggo in the academic year 2019/2020. The data of this research were obtained through (1) observation sheet, to obtain information about teacher’s and the students’ activities and performance during the implementation of Reciprocal Teaching Method, (2) quiz, to identify whether the students had made progress in reading comprehension, and (3) questionnaire, to get information from the students whether the strategy applied could motivate the students to actively involve during the teaching and learning process. The result of the research showed that the Reciprocal Teaching Method in the teaching-learning of reading comprehension was effective in improving the students’ reading comprehension. The improvement was indicated by the increase of the students’ average score throughout the cycle of action that was 72.63 in the preliminary study; 79.88 in the test of Cycle 1. Besides, students were motivated and active in the class using the method in terms of learning to work together and to help each other in a group with different competence, which was showed by the result of their works.